Dinuclear (arene)ruthenium complexes containing a chiral-at-phosphorus phosphanido bridge - Tschan, Mathieu J. L.; Süss-Fink, Georg; Cherioux, Frederic; Therrien, Bruno (My University, 2007)
The unsatd. diruthenium cation [(?6-C6Me6)(?6-p-iPrMeC6H4)Ru2(?2-H)3][BF4] reacts with Ph2P(CH2)3Ph to give the phosphido complex [(?6-C6Me6)(?6-p-iPrMeC6H4)Ru2{?2-PPh(CH2)3Ph}(?2-H)2][BF4] (1[BF4], 38% yield), which contains a stereogenic P atom in the bridge, and benzene. Heating of 1[BF4] in bromobenzene gives the 1st chiral-at-P diruthenium complex [(?6-C6Me6)Ru2(?2-PPh(CH2)3-?6-Ph)(?2-Br)2][BF4] (3[BF4], 30%) due to the replacement of the p-cymene ligand by the Ph group at the pendant arm and hydrido bridges by bromido bridges. The single-crystal x-ray structure anal. of [3][BF4] reveals a racemic mixt. of both enantiomers (RP)-3 and (SP)-3 in the crystal. Similarly, the reaction of [(?6-C6Me6)(?6-p-iPrMeC6H4)Ru2(?2-H)3][BF4] and the enantiopure phosphine (R)-Ph2P(CH2)2CHMePh yields [(?6-C6Me6)(?6-p-iPrMeC6H4)Ru2{?2-(R)-PPh(CH2)2CHMePh}(?2-H)2][BF4] (4[BF4], 38%) as a mixt. of diastereomers. An optically active mixt. (de = 4%) of phosphido-bridged complexes [(?6-C6Me6)Ru2{?2-(R)-PPh(CH2)2CHMe-?6-Ph}(?2-Br)2][BF4] (6[BF4], 40%), contg. the (RC,SP) and (RC,RP) diastereomers, was obtained upon heating of 4[BF4] in bromobenzene. The mol. structure of [6][BF4] reveals that the two diastereomers (RC,SP)-6 and (RC,RP)-6 exist as two conformers. The nonchiral-at-P analogs [(?6-C6Me6)2Ru2{?2-PPh(CH2)3Ph}(?2-H)2][BF4] (2[BF4]) and [(?6-C6Me6)2Ru2{?2-(R)-PPh(CH2)2CHMePh}(?2-H)2][BF4] (5[BF4]) also were synthesized and structurally characterized by single-crystal x-ray structure analyses. [on SciFinder(R)]
Keywords: trihydrido bridged dinuclear areneruthenium substitution phosphine tethered phenylalkyl; crystal structure dinuclear tethered arenephosphido ruthenium bridge chiral nonchiral; mol structure dinuclear tethered arenephosphido ruthenium bridge chiral nonchiral; dinuclear tethered arenephosphido ruthenium bridge chiral nonchiral prepn